2017
DOI: 10.1113/jp274269
|View full text |Cite
|
Sign up to set email alerts
|

Baroreflex dysfunction and augmented sympathetic nerve responses during mental stress in veterans with post‐traumatic stress disorder

Abstract: Key pointsr Patients with post-traumatic stress disorder (PTSD) are at a significantly higher risk of developing hypertension and cardiovascular disease. The mechanisms underlying this increased risk are not known.r Studies have suggested that PTSD patients have an overactive sympathetic nervous system (SNS) that could contribute to cardiovascular risk; however, sympathetic function has not previously been rigorously evaluated in PTSD patients.r Using direct measurements of sympathetic nerve activity and pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
104
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(114 citation statements)
references
References 73 publications
(136 reference statements)
7
104
3
Order By: Relevance
“…Indeed, an increase in blood pressure values and arterial rigidity results from an inflammatory endothelial damage. Proinflammatory cytokines increase peripheral resistances, decrease vagal sensitivity, and induce SRAA dysfunction (Park et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, an increase in blood pressure values and arterial rigidity results from an inflammatory endothelial damage. Proinflammatory cytokines increase peripheral resistances, decrease vagal sensitivity, and induce SRAA dysfunction (Park et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Park et al . () also hypothesized that a baroreflex dysfunction might play a role in SNS overactivation during mental stress in PTSD subjects, increasing their risk of cardiovascular diseases and hypertension. In their study, for the first time, muscle sympathetic nerve activity (MSNA) was directly assessed in PTSD subjects during rest and mental stress conditions.…”
mentioning
confidence: 99%
“…Additionally, Park et al . () assessed MSNA during a cold pressor test (CPT) that elicits a non‐baroreflex‐mediated SNS activation. The authors found that the increases in MSNA, blood pressure and heart rate were not different between PTSD and control subjects suggesting that the SNS overactivity in PTSD is restricted to mental stress conditions and, importantly, is baroreflex‐mediated.…”
mentioning
confidence: 99%
See 2 more Smart Citations